PENGABDIAN MASYARAKAT MELALUI PELATIHAN PEMASARAN DIGITAL MENGGUNAKAN ECOMMERCE SHOPEE PADA UMKM MAJUN JAYA DI KP. PASIR POGOR KABUPATEN BEKASI - Istiqomah, Anisah; Kartika, Dewi; Safira, Occha putrie; harisandi, Prasetyo (Jurnal Pengabdian Kepada Masyarakat Patikala, 2024)
Currently, the use of Internet technology is one way to encourage the development of the MSME market because in this digital era, it is appropriate for MSME players to market their products through digital marketing so that the products produced can be widely known by consumers. Digital marketing strategy Using Shopee e-commerce as an online marketing tool has several benefits for sellers. These include time flexibility, no operational costs, no need for advertising because the marketplace platform has its own advertising strategy, no rental fees, and users only need to register their online shop. The implementation method is carried out by socializing and training through material presentation, training on creating a Shopee merchant account, taking pictures and product descriptions as well as conducting live streaming and account management. The results obtained from this community service activity, partners as SMEs in Majun Jaya, who previously did not know about digital marketing and the benefits of selling through Shopee e-commerce, are now starting to market their products using e-commerce.